Financial Barriers to Women-Led Enterprises in South Africa: Insights from the Wefis Model - Sisanda Ngubane; Kombi Sausi (School of Business, IPB University (SB-IPB), 2026)
Background: Women-led enterprises play a transformative role in addressing unemployment and inequality. However, these businesses in South Africa face complex barriers, including exclusion from formal financial systems, a lack of institutional support, and gendered socio-cultural norms.Purpose: This study aims to identify and analyse the financial and institutional challenges affecting women entrepreneurs, while proposing adaptive strategies through the development of the Women's Entrepreneurial Finance and Institutional Support (WEFIS) Model.Design/methodology/approach: A qualitative case study methodology was used, involving semi-structured interviews with 12–15 women entrepreneurs in Durban and Gauteng. Data were analysed using reflexive thematic analysis supported by NVivo.Finding/Result: Four key domains emerged: structural finance barriers, institutional gaps, adaptive social capital strategies, and transformational impact pathways. Women entrepreneurs use informal peer networks and social capital to overcome systemic exclusion, though scalability remains limited.Conclusion: Women entrepreneurs develop creative coping strategies in response to exclusion, generating socio-economic gains such as community upliftment and gender-based empowerment. However, policy reforms must address systemic barriers to achieving impact at scale.Originality/value (state of the art): This study addresses these gaps by developing the Women’s Entrepreneurial Finance and Institutional Support (WEFIS) Model, an integrative framework combining the Resource-Based View, Institutional Theory, Social Capital Theory, and Empowerment Theory. Keywords: women entrepreneurship, financial inclusion, institutional support, empowerment, South Africa